2017
DOI: 10.17996/anc.17-00003
|View full text |Cite
|
Sign up to set email alerts
|

Energy Failure Hypothesis for Takotsubo Cardiomyopathy

Abstract: Takotsubo cardiomyopathy (TCM) is a transient myocardial stunning, typically showing apical ballooning. Although catecholamine toxicity, vasospasm, and disturbed microcirculation have been implicated, the precise pathophysiology of TCM is unknown. We present a two-step energy failure hypothesis which could explain the clinical course and pathogenesis. Sudden stress-induced increase in cardiac energy demand of normal subjects can be compensated for by additional supply of long chain fatty acids released from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Therefore, it has been considered that the pathophysiology of TTC is not a single etiology but a combination of several mechanisms in recent years. [27][28][29] However, there are only a few reports involving nuclear cardiology imaging for the variants of TTC 30,31 where the pathophysiology remains unclear. In this study, in the rTTC group, the decrease of the Tc-99m sestamibi uptake was observed in the area corresponding to the wall movement abnormalities in the acute phase as in the TTC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been considered that the pathophysiology of TTC is not a single etiology but a combination of several mechanisms in recent years. [27][28][29] However, there are only a few reports involving nuclear cardiology imaging for the variants of TTC 30,31 where the pathophysiology remains unclear. In this study, in the rTTC group, the decrease of the Tc-99m sestamibi uptake was observed in the area corresponding to the wall movement abnormalities in the acute phase as in the TTC group.…”
Section: Discussionmentioning
confidence: 99%
“…Single photon emission computed tomography (SPECT) was performed simultaneously in both groups in the respective acute and chronic phases. In the acute phase, SPECT was performed within a few days after admission (TTC: 3.0 [2.0-3.3] days vs rTTC: 3.0 [2.0-3.0] days, P = 0.72), and in the chronic phase, SPECT was performed approximately one month after admission (TTC: 33 [26][27][28][29][30][31][32][33][34][35][36][37] days vs rTTC: 35 days, P = 0.63).…”
Section: Study Populationmentioning
confidence: 99%
“…Long-chain fatty acid (LCFA) is the main sources of cardiomyocytes. TGs are hydrolyzed by adipose triglyceride lipase and released LCFAs which are oxidized in mitochondria to produce ATPs for cardiac energy ( 64 ). LCFAs are released on demand and delivered to the heart via the circulation and paracrine and used as energy substrates ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGs are hydrolyzed by adipose triglyceride lipase and released LCFAs which are oxidized in mitochondria to produce ATPs for cardiac energy ( 64 ). LCFAs are released on demand and delivered to the heart via the circulation and paracrine and used as energy substrates ( 64 ). In normal circumstances, the stress-induced increase in cardiac energy demand can be compensated from hydrolyzing TGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation